Editorial - RAMOS HOLGUÍN, BERTHA; Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In today’s world, there are strong pressures to dehumanize education. Educative institutions tend to use vocabulary that is more related to the industrialized world. Concepts such as methods, standards, effectiveness, competences, models are being naturalized. It seems to be that in education, day by day, institutions accept the criteria of efficiency without a question. In spite of this, teachers echo their voices to show that what educative institutions should focus on is increased humanism. In this volume of the Enletawa Journal, we acknowledge the voices of those teachers who want to understand their students' lives and their socio cultural realities. In other words, our authors in this volume are more interested in the who of teaching instead of the what of teaching.